Delayed management of Grade III blunt aortic injury: Series from a Level I trauma center. Issue 6 (June 2016) - Smeds, Matthew R.; Wright, Mark P.; Eidt, John F.; Moursi, Mohammed M.; Escobar, Guillermo A.; Spencer, Horace J.; Ali, Ahsan T.
Abstract : BACKGROUND: Blunt aortic injuries (BAIs) are traditionally treated as surgical emergencies, with the majority of repairs performed in an urgent fashion within 24 hours, irrespective of the grade of aortic injury. These patients are often underresuscitated and often have multiple other trauma issues that need to be addressed. This study reviews a single center's experience comparing urgent (<24 hours) thoracic endovascular aneurysm repair (TEVAR) versus delayed (>24 hours) TEVAR for Grade III BAI. METHODS: All patients undergoing TEVAR for BAI at a single institution between March 2004 and March 2014 were reviewed (n = 43). Patients with Grade I, II, or IV aortic injuries as well as those who were repaired with an open procedure or who lacked preoperative imaging were excluded from the analysis. Demographics, intraoperative data, postoperative survival, and complications were compared. RESULTS: During this period, there were 43 patients with blunt thoracic aortic injury. There were 29 patients with Grade III or higher aortic injuries. Of these 29 patients, 1 declined surgery, 2 were repaired with an open procedure, 10 underwent urgent TEVAR, and 16 had initial observation. Of these 16, 13 underwent TEVAR in a delayed fashion (median, 9 days; range, 2–91 days), and 3 died of non–aortic-related pathology. Comparing the immediate repair group versus the delayed repair group, there were no significant demographic differences. Trauma classification scores were similar, although patients in the delayed group had a higher number of nonaortic injuries. The 30-day survival was similar between the two groups (9 of 10 vs. 12 of 16), with no mortalities caused by aortic pathology in either group. CONCLUSION: Watchful waiting may be permissible in patients with Grade III BAI with other associated multisystem trauma. This allows for a repair in a more controlled environment. LEVEL OF EVIDENCE: Therapeutic study, level V.